Management of multivessel coronary artery disease in patients with non-ST-elevation myocardial infarction: a complex path to precision medicine - Angus A. W. Baumann; Aashka Mishra; Matthew I. Worthley; Adam J. Nelson; Peter J. Psaltis (SAGE Publishing, 2020)
Recent analyses suggest the incidence of acute coronary syndrome is declining in high- and middle-income countries. Despite this, overall rates of non-ST-elevation myocardial infarction (NSTEMI) continue to rise. Furthermore, NSTEMI is a greater contributor to mortality after hospital discharge than ST-elevation myocardial infarction (STEMI). Patients with NSTEMI are often older, comorbid and have a high likelihood of multivessel coronary artery disease (MVD), which is associated with worse clinical outcomes. Currently, optimal treatment strategies for MVD in NSTEMI are less well established than for STEMI or stable coronary artery disease. Specifically, in relation to percutaneous coronary intervention (PCI) there is a paucity of randomized, prospective data comparing multivessel and culprit lesion-only PCI. Given the heterogeneous pathological basis for NSTEMI with MVD, an approach of complete revascularization may not be appropriate or necessary in all patients. Recognizing this, this review summarizes the limited evidence base for the interventional management of non-culprit disease in NSTEMI by comparing culprit-only and multivessel PCI strategies. We then explore how a personalized, precise approach to investigation, therapy and follow up may be achieved based on patient-, disease- and lesion-specific factors.